2021
DOI: 10.4081/hr.2021.8961
|View full text |Cite
|
Sign up to set email alerts
|

Successful Use of Phlebotomy to Treat Severe Secondary Polycythemia Due to Chronic Lung Disease

Abstract: Secondary polycythemia (SP) occurs as a result of increase erythropoietin levels most commonly as a result of tissue hypoxia. Symptoms such as erythromelalgia, pruritis, and bleeding, which are frequently seen in polycythemia vera (PV), do not commonly occur in SP. Phlebotomy is considered one of the mainstays of therapy for PV but is rarely used for treatment of SP due to concern about worsening tissue hypoxia. We present the case of a patient with severe SP due to chronic hypoxic lung disease who presented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…However, the condition that should be excluded in the differential diagnosis at the very beginning of the diagnostic algorithm is the presence of secondary polycythemia (SP). It is observed that SP is often caused by tissue hypoxia and rarely by neoplasms that secrete erythropoietin (EPO) 6,7 , and is frequently associated with smoking and chronic obstructive pulmonary disease (COPD). It should be highlighted that, unlike primary polycythemia, the erythroid progenitor lineage of cells does not intrinsically exhibit a deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…However, the condition that should be excluded in the differential diagnosis at the very beginning of the diagnostic algorithm is the presence of secondary polycythemia (SP). It is observed that SP is often caused by tissue hypoxia and rarely by neoplasms that secrete erythropoietin (EPO) 6,7 , and is frequently associated with smoking and chronic obstructive pulmonary disease (COPD). It should be highlighted that, unlike primary polycythemia, the erythroid progenitor lineage of cells does not intrinsically exhibit a deficiency.…”
Section: Introductionmentioning
confidence: 99%